Action selection: Neuropeptidergic gates of behavior. - Louis, M.; Grunwald Kadow, I.C. (Current Biology, 2022)
Nervous systems continuously receive environmental signals with distinct behavioral meanings. To process ambiguous sensory inputs, neural circuits rely on hubs with compartmentalized synaptic structures. A new study has revealed how, in Drosophila larvae, this architecture with the local release of neuropeptides enables the control of flexible and context-dependent behavioral outcomes.